Circuit description and circuit simulation using C++ / Rozita Othman - Rozita , Othman (2005)
Techniques used for circuit description have often been treated differently from the methods used to simulate hardware. This report will attempt to demonstrate how a common platform, and hence a uniform environment, can be established to both describe and simulate hardware, using a programming paradigm known as object-oriented programming as supported by the C++ language. This paradigm is powerful enough to allow a hierarchical description of the hardware and at the same time provide an extensible method for its simulation. This report will provide a brief overview of C++ and its support for the object oriented programming paradigm.